?r-strongly almost summable sequences defined by Orlicz functions - Gungor, M; Et, M (Indian Nat Sci Acad, 2003)
The purpose of this paper is to introduce the space of sequences that are Delta(r)-strongly almost summable with respect to an Orlicz function. We give some relations related to these sequence spaces. It is also shown that if a sequence is Delta(r)-strongly almost summable with. respect to an Orlicz function, then it is Delta(r)-almost statistically convergent.
Keywords: difference sequence; statistical convergence; Orlicz function